2014
DOI: 10.7314/apjcp.2014.15.19.8101
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Mucin Component in Stage III Rectal Carcinoma Patients

Abstract: Background: Although mucinous adenocarcinoma has been recognized for a long time, whether it is associated with a poorer prognosis in colorectal cancer patients is still controversial. Many studies put emphasis on mucinous adenocarcinoma containing mucin component ≥50%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Several previous studies have demonstrated that positive lymphovascular invasion is a predictor of poorer OS in colorectal cancer patients [ 26 , 27 , 32 ]. Consistent with the published data, we also found that lymphovascular invasion is a significant predictor for OS in mucinous rectal cancer in univariate analysis, but it is not an independent prognostic factor for overall survival in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated that positive lymphovascular invasion is a predictor of poorer OS in colorectal cancer patients [ 26 , 27 , 32 ]. Consistent with the published data, we also found that lymphovascular invasion is a significant predictor for OS in mucinous rectal cancer in univariate analysis, but it is not an independent prognostic factor for overall survival in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown conflicting results regarding the prognosis of colorectal MAC compared to NMAC. Most studies, however, report a worse prognosis for rectal MAC [ 3 , 14 , 15 , 16 ] although a large cohort study by Hugen et al in 2015 [ 9 ] showed that from 1999 onwards the survival rates have been comparable, even after adjusting for type of preoperative treatment. Nevertheless, compared to NMAC, MAC has been associated with a poorer response to chemotherapy (CT) and chemo-radiotherapy (CRT) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mucinous adenocarcinoma (MUC) represents a histological subtype of CRC, containing a large amount of extracellular mucin in its structure. A large body of literature suggests that colorectal cases with a mucinous component carry a worse prognosis compared to those without such a component [ 31 - 33 ]. The mucinous component is more common in colorectal cancer cases that arise from inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%